2017
DOI: 10.1038/s41598-017-15075-4
|View full text |Cite
|
Sign up to set email alerts
|

A protease-resistant Escherichia coli asparaginase with outstanding stability and enhanced anti-leukaemic activity in vitro

Abstract: L-Asparaginases (ASNases) have been used as first line drugs for paediatric Acute Lymphoblastic Leukaemia (ALL) treatment for more than 40 years. Both the Escherichia coli (EcAII) and Erwinia chrysanthemi (ErAII) type II ASNases currently used in the clinics are characterized by high in vivo instability, short half-life and the requirement of several administrations to obtain a pharmacologically active concentration. Moreover, they are sensitive to proteases (cathepsin B and asparagine endopeptidase) that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 61 publications
(66 reference statements)
3
50
0
Order By: Relevance
“…We did not attempt, however, to correct for such discrepancies and used the coordinates directly as retrieved from the PDB. An exception was made for only one entry, 5mq5, representing the structure of the EcAII(N24S) mutant in complex with l ‐Asp . In that case, the original authors deposited the structure in which the occupancies for all atoms in l ‐Asp were set to 0.0 (despite evident presence of this ligand in the active sites), resulting in significantly incorrect contacts between the enzyme and the ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not attempt, however, to correct for such discrepancies and used the coordinates directly as retrieved from the PDB. An exception was made for only one entry, 5mq5, representing the structure of the EcAII(N24S) mutant in complex with l ‐Asp . In that case, the original authors deposited the structure in which the occupancies for all atoms in l ‐Asp were set to 0.0 (despite evident presence of this ligand in the active sites), resulting in significantly incorrect contacts between the enzyme and the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…An exception was made for only one entry, 5mq5, representing the structure of the EcAII(N24S) mutant in complex with L-Asp. 11 In that case, the original authors deposited the structure in which the occupancies for all atoms in L-Asp were set to 0.0 (despite evident presence of this ligand in the active sites), resulting in significantly incorrect contacts between the enzyme and the ligand. We reset the occupancies of L-Asp to 1.0 and performed 10 cycles of refinement with the program Refmac5 12 against structure factors deposited in the PDB.…”
Section: L-asparaginase Structures Included In the Analysismentioning
confidence: 99%
“…ASNase N24G mutant was resistant to AEP cleavage but was substantially less active (relative activity 45%). This residue (N24) is not directly involved in catalysis but it is responsible for active-site stabilization (Maggi et al, 2017).…”
Section: Protein Engineering For Improvement Of L-asparaginase Therapmentioning
confidence: 99%
“…Using molecular dynamics simulations the N24S mutation was proposed and a new ASNase showing resistance to proteases derived from leukemia cells was obtained, which retained all original enzymatic activity (Maggi et al, 2017). The improved biochemical characteristic of N24S provides a potential alternative to improving outcome in childhood ALL treatment.…”
Section: Protein Engineering For Improvement Of L-asparaginase Therapmentioning
confidence: 99%
“…a minor L-glutaminase activity), immunogenic properties of a bacterial protein, and limited in vivo stability of the enzyme. Thus continuous efforts to improve these therapeutic preparations are ongoing, focused on better understanding of the molecular basis of the activity and specificity of the enzyme 1012 , as well as on inventing novel ways of therapeutic application 9 . While performing crystallographic studies of EcAII as part of such efforts, we frequently observed citrate anions located in the enzyme active site.…”
Section: Introductionmentioning
confidence: 99%